Immunogenetics of prostate cancer and benign hyperplasia – The potential use of an hla-g variant as a tag snp for prostate cancer risk - Zambra, F. M.B.; Biolchi, V.; De Cerqueira, C. C.S.; Brum, I. S.; Castelli, E. C. [UNESP]; Chies, J. A.B. (Wiley, 2016)
Human leukocyte antigen G (HLA-G) is an immunomodulatory molecule with important roles both physiologically as well as an escape mechanism of cancer cells. In this study, we evaluated the impact of eight polymorphisms at the 3′ untranslated region (3′ UTR) of the HLA-G gene in the development of prostate cancer (PCa) and benign prostatic hyperplasia (BPH). A total of 468 DNA samples of Brazilian men predominantly Euro-descendant with PCa (N = 187), BPH (N = 152) and healthy control individuals (N = 129) were evaluated. The HLA-G 3′ UTR region was amplified by polymerase chain reaction (PCR), sequenced and genotyped to identify the 14 bp insertion/deletion (rs371194629), +3003T/C (rs1707), +3010C/G (rs1710), +3027A/C (rs17179101), +3035C/T (rs17179108), +3142G/C (rs1063320), +3187A/G (rs9380142) and +3196C/G (rs1610696) polymorphisms. Regression logistic and chi-square tests were performed to verify the influence of single nucleotide polymorphisms (SNPs) in PCa and/or BPH susceptibility, as well as in PCa progression (clinicopathological status). Our data showed the UTR-4 haplotype as a risk factor to PCa in comparison with control [odds ratio (OR) 2.35, 95% confidence interval (CI) 1.39–3.96, Padjusted = 0.003) and BPH groups (OR 1.82, 95% CI 1.15–2.86, Padjusted = 0.030). Further, the ‘non-14bp Ins_ + 3142G_+3187A’ haplotype (OR 1.56, 95% CI 1.10–2.20, Padjusted = 0.036), the +3003CT genotype (OR 4.44, 95% CI 1.33–4.50, Padjusted = 0.032) and the +3003C allele (OR 2.33, 95% CI 1.38–3.92, Padjusted = 0.016) also conferred susceptibility to PCa. Our data suggest an important influence of HLA-G 3′ UTR polymorphisms in PCa susceptibility and support the use of the +3003 variant as a tag SNP for PCa risk.
Keywords: +3003 locus; 3′ untranslated region; Benign prostatic hyperplasia; Haplotype; Prostate cancer; Untranslated region-4